The Political Interest Of Millenial Generation - Katili, Andi Yusuf; Ida Ri'aeni; Geofakta Razali; Shohib Muslim; Hairus Hairus (Journal of Research and Development on Public Policy, 2023)
This article is based on the existence of researchers' participation in the democracy system in Indonesia, especially in Garut District. The study aims to determine the voter participation of three generations (generation X, generation Y, and generation Z) from the perspective of lack of political interest and dissatisfaction with candidates. This study uses descriptive and verification methods with a quantitative approach. With a sample of 145 respondents spread out of 3 villages (Banjarwangi Village, Jayabakti Village, and Bojong Village), the location of the research is the region with the largest population and voting rights in the Banjarwungi District District of Garut. Data analysis method: path analysis using SPSS software The results of the study showed the magnitude of the total influence of ignorance or lack of political interest and dissatisfaction with the selection of candidates against electoral participation in Generation X was shown by the size of the determination coefficient (r2) = 0.488, or 46.7%; in Generation Y, the greatness of the factor of determination (R2) = 0.510, or 51%; and in Generation Z, the measurement of the deterrence coefficient (R2) = 0.793, or 72.3%. So it was concluded that the model formed belongs to the strong category, so in this study, the variable of ignorance, lack of political interest, or dissatisfaction with the choice was used to measure the participation of voters in the Banjarwangi Garut district.